Evaluation of Effects of Topical Melatonin Application on Osseointegration of Dental Implant: An Experimental Study - Dundar, Serkan; Yaman, Ferhan; Saybak, Arif; Ozupek, M. Fatih; Toy, Vesile Elif; Gul, Mehmet; Ozercan, I. Hanifi (Allen Press Inc, 2016)
The aim of the present study was to evaluate the effect of local melatonin application during surgery on bone implant connection (BIC) in rabbit tibiae. Six 0.8- to 1-year-old male New Zealand rabbits were divided into 3 groups: (1) a control group (CG) in which rabbits were not treated with additive materials and only implant integration was executed; (2) a melatonin dose 1 (MLT D-1) group in which rabbits were treated with 1.2 mg of melatonin locally before implant placement into the rabbits' tibiae; and (3) a melatonin dose 2 (MLT D-2) group in which rabbits were treated with 3 mg melatonin locally before implant placement into the rabbits' tibiae. Four weeks after the procedure, the rabbits were euthanized; their tibiae were dissected from muscles and soft tissues, fixed with formaldehyde, and later embedded in methacrylate. Histologic and histomorphometric analyses were then performed under light microscopy. Following this, BIC was detected histomorphometrically, and P<.05 was considered statistically significant. Results showed that the highest BIC percentage was detected in MLT D-2, with a mean value of 39.46% +/- 0.78, as compared with a mean value of 33.89% +/- 0.92 in group MLT D-1 and 27.42% +/- 0.89 in CG. Similarly, the mean BIC percentage of the MLT D-2 group was the highest among the three, with the mean BIC percentage of the MLT D-1 still registering as higher than CG. Within the limitations of this rabbit study, it appears that local melatonin application during implant surgery may improve BIC.
Keywords: bone implant connection; implant; local melatonin; rabbit; bone